Comparison of ventilation defects quantified by Technegas SPECT and hyperpolarized 129Xe MRI - Radadia, Nisarg; Friedlander, Yonni; Priel, Eldar; Konyer, Norman B.; Huang, Chynna; Jamal, Mobin; Farncombe, Troy; Marriott, Christopher; Finley, Christian; Agzarian, John; Dolovich, Myrna; Noseworthy, Michael D.; et al. (Frontiers in Physiology, 2023)
Introduction: The ideal contrast agents for ventilation SPECT and MRI are Technegas and 129Xe gas, respectively. Despite increasing interest in the clinical utility of ventilation imaging, these modalities have not been directly compared. Therefore, our objective was to compare the ventilation defect percent (VDP) assessed by Technegas SPECT and hyperpolarized 129Xe MRI in patients scheduled to undergo lung cancer resection with and without pre-existing obstructive lung disease. Methods: Forty-one adults scheduled to undergo lung cancer resection performed same-day Technegas SPECT, hyperpolarized 129Xe MRI, spirometry, and diffusing capacity of the lung for carbon monoxide (DLCO). Ventilation abnormalities were quantified as the VDP using two different methods: adaptive thresholding (VDPT) and k-means clustering (VDPK). Correlation and agreement between VDP quantified by Technegas SPECT and 129Xe MRI were determined by Spearman correlation and Bland-Altman analysis, respectively. Results: VDP measured by Technegas SPECT and 129Xe MRI were correlated (VDPT: r=0.48, p=0.001; VDPK: r=0.63, p<0.0001). A 2.0% and 1.6% bias towards higher Technegas SPECT VDP was measured using the adaptive threshold method (VDPT: 23.0±14.0% vs. 21.0±5.2%, p=0.81) and k-means method (VDPK: 9.4±9.4% vs. 7.8±10.0%, p=0.02), respectively. For both modalities, higher VDP was correlated with lower FEV1/FVC (SPECT VDPT: r=-0.38, p=0.01; MRI VDPK: r=-0.46, p=0.002) and DLCO (SPECT VDPT: r=-0.61, p<0.0001; MRI VDPK: r=-0.68, p<0.0001). Subgroup analysis revealed that VDP measured by both modalities was significantly higher for participants with COPD (n=13) than those with asthma (n=6; SPECT VDPT: p=0.007, MRI VDPK: p=0.006) and those with no history of obstructive lung disease (n=21; SPECT VDPT: p=0.0003, MRI VDPK: p=0.0003). Discussion: The burden of ventilation defects quantified by Technegas SPECT and 129Xe MRI VDP was correlated and greater in participants with COPD when compared to those without. Our observations indicate that, despite substantial differences between the imaging modalities, quantitative assessment of ventilation defects by Technegas SPECT and 129Xe MRI is comparable.